Did the introduction of the Euro have an impact on inflation uncertainty?: an empirical assessment - Hartmann, Matthias; Herwartz, Helmut (Macroeconomic dynamics, 2014)
We compare inflation uncertainty in distinguished groups of economies. Results indicate that during the recent financial crisis the global inflation climate has become markedly more uncertain than previously. We document that in comparison to other economies, member states of the European Monetary Union are less exposed to inflation uncertainty. Three European Union members that are not part of the monetary union and five other OECD member economies serve as control groups. With regard to the quantification of inflation uncertainty, results are robust over a set of alternative estimates of the latent inflation risk processes.